2019
DOI: 10.1097/gme.0000000000001378
|View full text |Cite
|
Sign up to set email alerts
|

Opinions and main sources of information about menopause among middle-aged Brazilian women

Abstract: Objectives: The aim of this study was to evaluate women's opinions about menopause and the sources of information they use to deepen their understanding of the topic. Methods: Population-based study with 749 Brazilian women aged 45 to 60 years. The answers to the question “What is menopause?” were typed and coded, and categories that emerged from the interviewees’ own speech were created. The answers to the question: “Where or from whom did you get info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In addition, the results of this survey showed that the main sources of MHT-related knowledge among women were menopausal women around them, medical units, and internet-based pathways; 42% of the respondents’ knowledge originated from medical units, and most of the respondents’ menopause-related knowledge came from nonmedical units. The results of a cross-sectional survey conducted in Brazil showed that the main sources of women’s knowledge about menopause were close friends, family members, and relatives, which is consistent with the results of this study [ 43 ]. In recent years, internet information technology has developed rapidly, and the internet has the advantages of convenience, privacy, promotion, etc., so that women can receive menopause-related knowledge anytime and anywhere [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the results of this survey showed that the main sources of MHT-related knowledge among women were menopausal women around them, medical units, and internet-based pathways; 42% of the respondents’ knowledge originated from medical units, and most of the respondents’ menopause-related knowledge came from nonmedical units. The results of a cross-sectional survey conducted in Brazil showed that the main sources of women’s knowledge about menopause were close friends, family members, and relatives, which is consistent with the results of this study [ 43 ]. In recent years, internet information technology has developed rapidly, and the internet has the advantages of convenience, privacy, promotion, etc., so that women can receive menopause-related knowledge anytime and anywhere [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…The most frequently used information sources were audiovisual media, obstetricians, friends, family and the internet. In contrast, a study conducted on middle-aged Brazilian women found that the most frequently used sources of information were friends, family, physicians and audiovisual media, while the least frequently used source was the internet [ 21 ]. However, this difference is most likely related to the data being gathered in 2012 and 2013, meaning that public access to the internet was limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference is most likely related to the data being gathered in 2012 and 2013, meaning that public access to the internet was limited. Moreover, there were few discussions about menopause in the Brazilian media, which was used much less as a source compared with friends, family and physicians [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Websites specialising in menopause are promising tools for providing knowledge, and forums on menopause can facilitate interaction between women further enhancing learning. The availability of websites in different languages, can also extend access to relevant information on menopause to women from varying backgrounds [32,33]. Tao et al, [34] found that women valued the information they received from websites and regarded it equal to the quality of information received from health providers.…”
Section: Discussionmentioning
confidence: 99%